KEPUASAN KERJA MEMEDIASI PENGARUH WORKPLACE SPIRITUALITY DAN RELIGIOSITY TERHADAP KINERJA APARATUR SIPIL NEGARA (STUDI KASUS PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBERDAYA MANUSIA KABUPATEN PESISIR SELATAN) - Ricky Saputra; Herri; Yulihasri (Halu Oleo University, 2024)
This study aims to analyze the effect of Workplace Spirituality, and religiosity on the performance of civil servants with job satisfaction as a mediating variable. This research is quantitative research. This type of research is correlational research. A correlational investigation is an identification of important factors that are